Understanding Cervical Cancer Prevention and Practice of Human Papillomavirus Vaccination: A Study Among Medical Students of Ahmedabad (GAIMS Journal of Medical Sciences, 2026)
Background: Early HPV vaccination can significantly reduce the burden of cervical cancer, yet most of India’s population remains unprotected. Medical students, as future healthcare advocates, are key to improving HPV vaccination through their awareness and practice. This study aims to assess the socio-demographic profile of participants, measure their awareness about cervical cancer and its prevention, vaccination status, and to correlate these findings with socio-demographic details.Material and Methods: A cross sectional study was conducted among 181 medical students of Ahmedabad using a standardized, validated questionnaire consisting of open ended, Yes/No/Don’t know and MCQ questions. Statistical analysis was performed and appropriate tests were applied.Results: The study included 128 females (70.7%)  and 53 males (29.3% ) with a mean age of 19.85 ± 1.60 years. While 82.3% identified cervical cancer as a leading cause of death among women, only 56.9% were aware that HPV affects both genders. Although 77.3% were aware of the HPV vaccine, correct knowledge about the recommended age group and dose schedule was low (14.9% and 5.5%respectively). Only 43 students (23.75%) were vaccinated with significantly more females being vaccinated (z = 2.5297, p = 0.0114). Among unvaccinated participants, the major barriers to HPV vaccination included lack of knowledge (31.15%), limited access to vaccine (10%), and lack of motivation (6.52%).Conclusion: Although awareness about HPV infection and cervical cancer among medical students is good, there is a lack of awareness and knowledge about prevention of cervical cancer. Practice of HPV vaccination among medical students was found to be low.